2018
DOI: 10.1111/iej.12883
|View full text |Cite
|
Sign up to set email alerts
|

Calcium chloride‐enriched calcium aluminate cement promotes in vitro osteogenesis

Abstract: For CAC with the lower CaCl content, the use of Bi O was detrimental for osteoblastic cell survival and differentiation compared to ZnO, while CAC with the higher CaCl content supported the acquisition of the osteogenic cell phenotype in vitro regardless of the radiopacifier used. Thus, CAC with 10% CaCl would potentially promote bone repair in the context of endodontic therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 41 publications
3
11
0
Order By: Relevance
“…Therefore, calcium deposits are an indication of successful in vitro bonelike nodule formation that can specifically be stained bright orange-red using Alizarin Red S dye. The results showed that ZnO addition in CACH significantly inhibited matrix mineralization, and these findings agree with the observations of Togari et al (1993) and Vicuna et al (2019) showing that zinc exposure reduces calcium content and inhibits matrix mineralization in osteogenic cell cultures, yet it induces alkaline phosphatase activity and gene expression of osteoblast markers (Togari et al 1993;Castro-Raucci et al 2018;Vicuna et al 2019).…”
Section: Discussionsupporting
confidence: 86%
“…Therefore, calcium deposits are an indication of successful in vitro bonelike nodule formation that can specifically be stained bright orange-red using Alizarin Red S dye. The results showed that ZnO addition in CACH significantly inhibited matrix mineralization, and these findings agree with the observations of Togari et al (1993) and Vicuna et al (2019) showing that zinc exposure reduces calcium content and inhibits matrix mineralization in osteogenic cell cultures, yet it induces alkaline phosphatase activity and gene expression of osteoblast markers (Togari et al 1993;Castro-Raucci et al 2018;Vicuna et al 2019).…”
Section: Discussionsupporting
confidence: 86%
“…The term "hydraulic" is used to define the setting reaction (i.e., with water), and the ability to set and then be stable in a wet environment, which is crucial. For this reason, a sub-classification of hydraulic silicate cements has been used to differentiate materials such as Portland cement, which is a silicate, from calcium aluminates that are also being proposed as dental materials (17)(18)(19). These materials are all hydraulic but have different chemistries otherwise.…”
Section: Discussionmentioning
confidence: 99%
“…The following cements were used: 1) CACz 15 , 18 ; 2) CACb with Bi 2 O 3 and 2.8% CaCl 2 ; 3) CACb+ with Bi 2 O 3 and 10% CaCl 2 ; and 4) MTA (Angelus, Londrina, PR, Brazil). The CAC powders were mixed with sterile water (3:1, v/v).…”
Section: Methodsmentioning
confidence: 99%
“…Aiming to improve the biological and clinical properties of CACz, we proposed raising the CaCl 2 content to increase calcium release and enhancing its radiopacity by replacing ZnO by Bi 2 O 3 17 , 18 . In osteoblastic cells, CAC with Bi 2 O 3 and increased CaCl 2 content supported cell differentiation and matrix mineralization 18 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation